Teacher's pets - Dodds, Dayle Ann.; Hafner, Marylin (Candlewick Press, 2006)
A teacher invites her students to bring their pets in each Monday for sharing day, but by the end of the year, she has a classroom full of "forgotten" animals.
A teacher invites her students to bring their pets in each Monday for sharing day, but by the end of the year, she has a classroom full of "forgotten" animals.
Keywords: Schools / Fiction.; Pets / Fiction.